Joint and independent neurotoxic effects of early life exposures to a chemical mixture: A multi-pollutant approach combining ensemble learning and G-computation. Issue 5 (October 2019) - Oulhote, Youssef; Coull, Brent; Bind, Marie-Abele; Debes, Frodi; Nielsen, Flemming; Tamayo, Ibon; Weihe, Pal; Grandjean, Philippe
Abstract : Background: Exposure to mercury (Hg) is associated with adverse developmental effects. However, Hg occurs with a multitude of chemicals. We assessed the associations of developmental exposure to multiple pollutants with children's neurodevelopment using a novel approach. Methods: Hg, polychlorinated biphenyls (PCBs), and perfluoroalkyl substances (PFASs) were measured in maternal and children's blood at 5 years (n = 449 and 419). At 7 years, children were administered Boston Naming Test (BNT) and the Strengths and Difficulties Questionnaire (SDQ). We used the G-formula combined with SuperLearner to estimate independent and joint effects of chemicals at both ages. We constructed flexible exposure-response relationships and assessed interactions. Results: Most chemicals showed negative relationships with BNT scores. An interquartile range (IQR) increase in maternal Hg and perfluorooctanoic acid (PFOA) was associated with 0.15 standard deviation (SD) (95% confidence interval [CI] = –0.29, –0.03) and 0.14 SD (95% CI = –0.26, –0.05) lower scores in BNT, whereas a joint IQR increase in the mixture of chemicals was associated with 0.48 SD (95% CI = –0.69, –0.25) lower scores in BNT. An IQR increase in PFOA was associated with 0.11 SD (95% CI = 0.02, 0.26) higher total SDQ difficulties scores. Maternal ∑PCBs concentrations were associated with lower SDQ scores (β = –0.09 SD; 95% CI = –0.19, 0), whereas 5 years ∑PCBs showed a negative association (β = –0.09 SD; 95% CI = –0.21, 0). Finally, a joint IQR increase in the mixture was associated with 0.22 SD (95% CI = 0.04, 0.4) higher SDQ scores. Conclusions: Using a novel statistical approach, we confirmed associations between prenatal mercury exposure and lower cognitive function. The potential developmental effects of PFASs need additional attention. Abstract : Supplemental Digital Content is available in the text.